"What does the university have to do with it?”: Perceptions of rape culture on campus and the role of university authorities - Orth, Z.; van Wyk, B.; Andipatin, M. (South African Journal of Higher Education, 2020)
In April 2016, the #Endrapeculture protests spread across South African university campuses. These protests raised awareness of university policies regarding rape and sexual assault cases on campus. The protesters accused the university management of perpetuating a rape culture through policies which reinforced victim-blaming and protected perpetrators of sexual assault. Through the use of hashtag campaigns and public demonstrations, the movement quickly gained momentum across social and mainstream media. This momentum served to put pressure on university administrations to be accountable for cases of sexual assault on campuses. Movements calling out universities for perpetuating a rape culture are not unique to South Africa; as similar movements have been initiated at other university campuses across the globe. This article examines the rape culture discourse that emerged on Facebook following the #Endrapeculture protests. Specifically, we look at how people perceived rape culture and the role of university management in handling sexual assault. Naturalistic observation was used on comments from public posts and articles from Facebook relating to the 2016 #Endrapeculture protest. These comments were subjected to qualitative content analysis. Two main themes are discussed in this article: Rape/Rape Culture and The Role of Universities and Law Enforcement. Many commenters indicated that cases of rape and sexual assault should be addressed by law enforcement and should not be handled by university management. We argue that rape culture education should be formalised in South Africa.